Building accessible destinations. Tourism, transport and disability in Europe - David Rodríguez Guillén; Juan Antonio Clemente Soler; Juan Carlos Solano Lucas (Social Sciences and Humanities Open)
Tourism is a strategic sector in Europe, and accessibility is not only a right but also represents a key element in achieving quality tourism. Thus, tourism can be understood as a matter of social justice and an integral strategy to improve destinations’ competitiveness and sustainability, as well as the overall tourist experience. Based on the understanding of accessibility as a fundamental principle in providing quality tourism that is free of discrimination, this study uses a structured questionnaire to comprehensively address key elements related to tourist accessibility. We identify potential actions for improvement; for example, making professionals in the field of accessibility available for consultation when creating tenders, improving aspects of European legislation, promoting best practices and information exchange, and improving sensitisation and awareness around this issue in society, the workplace, and educational institutions. In addition, the use of artificial intelligence or improved budget allocation at the European level could be highly useful.